Patterns of childhood immunization and all-cause mortality. Issue 48 (4th December 2017) - McCarthy, Natalie L.; Sukumaran, Lakshmi; Newcomer, Sophia; Glanz, Jason; Daley, Matthew F.; McClure, David; Klein, Nicola P.; Irving, Stephanie; Jackson, Michael L.; Lewin, Bruno; Weintraub, Eric
Highlights: Recommended childhood immunization schedule and all-cause mortality. Examined deaths among young children with respect to their vaccination patterns. Mortality rates were not significantly different between the patterns identified. No increased risk of mortality for fully vaccinated versus undervaccinated children. Findings support the safety of the schedule with regard to all-cause mortality. Abstract: Background: Evidence supports the safety of the recommended childhood immunization schedule as a whole. However, additional research is warranted as parents' refusing or delaying vaccinations has increased in recent years. All-cause mortality has been identified as a priority outcome to study in the context of the recommended immunization schedule. Methods: We included children born January 1, 2004 through December 31, 2009, enrolled in the Vaccine Safety Datalink (VSD) from birth through 18 months of age. We examined vaccination patterns during the first 18 months of life among 8 vaccines, and identified deaths occurring between 19 and 48 months of age. We excluded children with complex chronic conditions, contraindications to vaccination, and deaths due to injuries, congenital anomalies, or diseases with onset prior to 19 months of age. We calculated mortality rates among children with different patterns of immunization, and incidence rate ratios (IRR) using the Cox proportional hazards model for children vaccinated according to the schedule versus undervaccinated children, adjusting for outpatient healthcare utilization, influenza vaccination, sex, and VSD site. Results: Among 312, 388 children in the study, 199, 661 (64%) were vaccinated according to the schedule, and 112, 727 (36%) were delayed or not vaccinated for at least one vaccine dose. Of 18 deaths eligible for analysis, 11 occurred in children following the schedule (2.28 per 100, 000 person-years), and seven occurred in undervaccinated children (2.57 per 100, 000 person-years). Mortality rates among children following the schedule were not significantly different from those of undervaccinated children when excluding deaths with unknown causes (IRR = 1.29, 95% CI = 0.33–4.99), as well as when including deaths with unknown causes (IRR = 0.84, 95% CI = 0.32–2.99). Conclusion: Although there were few deaths, our results do not indicate a difference in risk of all-cause mortality among fully vaccinated versus undervaccinated children. Our findings support the safety of the currently recommended immunization schedule with regard to all-cause mortality.